2019
DOI: 10.1186/s12871-019-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Palonosetron versus ondansetron for prevention of nausea and vomiting after total abdominal hysterectomy under spinal anesthesia with intrathecal morphine: a double-blind, randomized controlled trial

Abstract: Background Hysterectomy is a widely performed surgery and neuraxial anesthesia with intrathecal morphine provides superior quality of recovery. Postoperative nausea and vomiting (PONV) is a frequent problem with intrathecal morphine use. Although palonosetron is effective for prevention of PONV after general anesthesia, its efficacy after neuraxial anesthesia has not been established. This study was conducted to compare the use of palonosetron with ondansetron for PONV prophylaxis in patients at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…However, the frequency of nausea/vomiting and the need for treatment were greater in the GA group compared to the SA group. In this regard, the results of similar studies (26,27) indicated that GA causes more nausea and vomiting than other methods, increasing the need for antiemetic medications. Nausea and vomiting in surgeries (e.g., hysterectomy) can put pressure on the intestines and the lower gastrointestinal tract, which can have adverse effects on the results of hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of nausea/vomiting and the need for treatment were greater in the GA group compared to the SA group. In this regard, the results of similar studies (26,27) indicated that GA causes more nausea and vomiting than other methods, increasing the need for antiemetic medications. Nausea and vomiting in surgeries (e.g., hysterectomy) can put pressure on the intestines and the lower gastrointestinal tract, which can have adverse effects on the results of hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have compared the efficacy of palonosetron plus dexamethasone to ondansetron plus dexamethasone, while the results appear to favor palonosetron plus dexamethasone, and the difference was not statistically significant. 83–88 …”
Section: Novel Chemoprophylaxismentioning
confidence: 99%
“…Abdominal hysterectomy is applicable for patients with obvious symptoms, no fertility requirements, or possible malignant changes [ 2 ]. A hysterectomy typically is performed under general anesthesia [ 3 ]. Research has indicated that postoperative stress is associated with factors such as the method of anesthesia and surgical procedures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%